Sanctifying Rites in Milton's A Masque Presented at Ludlow Castle, 1634. (March 2019) - Timmis, Patrick
This article seeks to challenge Stanley Fish's picture of the heroine of Milton's Comus as a complete and immaculate soul, and thus a static one with no need to grow. In conversation with Book II of Edmund Spenser's Faerie Queene, I argue that Milton presents the Christian virtues as developed through the ritual enactment of prevenient grace. Thus, the pattern for the Lady's growth into sanctified maturity is a ceremonial or even liturgical movement intended to lead masquers and audience heavenward.